Investigations of Mechanical Testing and its Effects on Lithium Ion Battery and Battery Pack for Electric Vehicle Application - Sonali Sabale; Deepak Watvisave; Vishwajeet Gaike; Ravikant Nanwatkar (International Journal of Fracture Mechanics and Damage Science, 2025)
This research delves into the comprehensive study of mechanical testing methodologies and their consequential impact on the structural integrity, safety, and performance of Lithium-Ion batteries (Li-ion) and battery packs designed for electric vehicle (EV) applications. The investigation aims to enhance the understanding of mechanical stressors' influence on the reliability and safety of energy storage systems crucial for the sustainable advancement of electric mobility. The paper opens with mechanical testing protocols that have already been established on single Li-ion cells. Various tests, including compression, puncture, and impact resistance evaluations, are conducted to simulate real-world scenarios during manufacturing, transportation, and operational phases. Through these tests, the vulnerabilities and failure modes of individual cells are meticulously examined, shedding light on potential areas for improvement in cell design and manufacturing processes. Extending the investigation to encompass complete battery packs, the research establishes testing procedures to simulate dynamic conditions encountered during electric vehicle usage. Vibrations, accelerations, and thermal cycling are systematically applied to assess the overall structural integrity of the battery pack, including its components such as connectors and cooling systems. Ideally, one would like to determine possible weak- or failure-modes due to mechanical stress under Furthermore, the study endeavors to establish a correlation between mechanical stresses and the electrical and thermal performance of Li-ion batteries. Experimental data is analyzed to quantify the impact of mechanical testing on critical parameters such as capacity retention, internal resistance, and temperature regulation mechanisms. This holistic approach aims to provide insights into the interdependencies between mechanical stresses and the long-term performance and safety of Li-ion batteries in the context of electric vehicles. The anticipated outcomes of this research are expected to inform the development of advanced battery pack designs, manufacturing processes, and safety protocols for electric vehicles. By uncovering the intricate relationship between mechanical stressors and the performance of Li-ion batteries, the research aims to contribute to the continuous improvement of electric vehicle technologies, fostering their wider adoption and ensuring the durability and safety of energy storage systems in the evolving landscape of sustainable transportation.
Keywords: Impact Test; Lithium Ion Battery; drop test; mechanical integrity; mechanical stress